1992
DOI: 10.1063/1.106791
|View full text |Cite
|
Sign up to set email alerts
|

Optical emission properties of semi-insulating GaAs grown at low temperatures by molecular beam epitaxy

Abstract: We have used cathodoluminescence (CL) and photoluminescence spectroscopy to observe deep-level states in GaAs grown at low-substrate temperatures by molecular beam epitaxy (LT GaAs) and the evolution of these states upon annealing. The as-grown material shows intense deep-level emissions which can be associated with an excess concentration of arsenic, mostly present as As-antisite and As-interstitial defects. These emissions subside with annealing for a few minutes at temperatures above 450 °C. CL measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…For the Si-doped samples (b) and (c) respectively with 0.28×10 18 cm -3 and 2.10×10 18 cm -3 , we note also the presence of the wide band and only one fine structure at high energy. The decrease of the wide band PL intensity is noted by increasing the silicon content, this effect is firstly attributed to the deep nitrogen localized states, but recently, we found that the same wide band was also observed by Viturro et al [16] in GaAs at low growth temperature. We remind that the growth temperature of GaAsN is decreased to avoid the nitrogen evaporation, that causes a three-dimensional growth and then the formation of deep defects.…”
Section: Methodssupporting
confidence: 61%
“…For the Si-doped samples (b) and (c) respectively with 0.28×10 18 cm -3 and 2.10×10 18 cm -3 , we note also the presence of the wide band and only one fine structure at high energy. The decrease of the wide band PL intensity is noted by increasing the silicon content, this effect is firstly attributed to the deep nitrogen localized states, but recently, we found that the same wide band was also observed by Viturro et al [16] in GaAs at low growth temperature. We remind that the growth temperature of GaAsN is decreased to avoid the nitrogen evaporation, that causes a three-dimensional growth and then the formation of deep defects.…”
Section: Methodssupporting
confidence: 61%
“…The quenched luminescence intensity of the LT GaAs annealed at 600°C can be dominated by the overlapping Schottky barriers, instead of the reduced point defect. 17 The PL and TEM results clearly show that the luminescence property of annealed LT GaAs is directly related to the spacing between As clusters, and it strongly supports the buried Schottky barrier model.…”
supporting
confidence: 53%
“…The precipitate density was estimated to be 1.5ϫ10 17 cm Ϫ3 , with cluster center-to-center spacing of about 8.7 nm in the LT-GaAs regions. The As/ GaAs interfaces show a very high nonradiative recombination rate, 17 which dramatically reduces radiative recombination probabilities and carrier lifetime. Therefore, the sample shows a featureless spectral shape in Fig.…”
mentioning
confidence: 99%
“…The LT-GaAs exhibits very weak photoluminescence ͑PL͒ and extremely short carrier lifetimes. [5][6][7] Upon annealing, the moderately conducting LT-GaAs becomes semiinsulating, and this increase of resistivity is accompanied by the reduction in point defect densities and the formation of As clusters. 3,[8][9][10][11] The mechanism responsible for the semiinsulating properties of LT-GaAs is still under debate, despite a large number of studies on this topic.…”
mentioning
confidence: 99%